Small vault RNA1-2 modulates expression of cell membrane proteins through nascent RNA silencing - Alagia, A; Tereňová, J; Ketley, RF; Di Fazio, A; Chelysheva, I; Gullerova, M (Rockefeller University Press, 2023)
Gene expression can be regulated by transcriptional or post-transcriptional gene silencing. Recently, we described nuclear nascent RNA silencing that is mediated by Dicer-dependent tRNA-derived small RNA molecules. In addition to tRNA, RNA polymerase III also transcribes vault RNA, a component of the ribonucleoprotein complex vault. Here, we show that Dicer-dependent small vault RNA1-2 (svtRNA1-2) associates with Argonaute 2 (Ago2). Although endogenous vtRNA1-2 is present mostly in the cytoplasm, svtRNA1-2 localises predominantly in the nucleus. Furthermore, in Ago2 and Dicer knockdown cells, a subset of genes that are up-regulated at the nascent level were predicted to be targeted by svtRNA1-2 in the intronic region. Genomic deletion of vtRNA1-2 results in impaired cellular proliferation and the up-regulation of genes associated with cell membrane physiology and cell adhesion. Silencing activity of svtRNA1-2 molecules is dependent on seed-plus-complementary-paired hybridisation features and the presence of a 5-nucleotide loop protrusion on target RNAs. Our data reveal a role of Dicer-dependent svtRNA1-2, possessing unique molecular features, in modulation of the expression of membrane-associated proteins at the nascent RNA level.